1999
DOI: 10.1172/jci5286
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride enrichment of HDL enhances in vivo metabolic clearance of HDL apo A-I in healthy men

Abstract: The inverse relationship between plasma HDL cholesterol concentrations and the risk of cardiovascular disease is well accepted (1, 2). There is a large body of evidence indicating that variations in plasma HDL cholesterol concentrations are inversely related to plasma triglyceride (TG) levels (3, 4). Hence, one of the most frequent metabolic abnormalities accompanying reduced plasma HDL cholesterol levels is hypertriglyceridemia. Apo A-I, the major protein of HDL, is a crucial structural and functional compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
2
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(146 citation statements)
references
References 43 publications
8
134
2
2
Order By: Relevance
“…Atorvastatin appears to inhibit CETP activity in humans, which should decrease HDL triglycerides, 31 and fails to alter hepatic and lipoprotein lipase levels in the rabbit model, 22 which should leave the HDL triglyceride content unchanged. Nonetheless, triglyceride enrichment of HDL has previously been shown to enhance HDL apoA-I catabolism in vivo, 32 and combined with other drug-induced effects, could have contributed to the enhanced HDL apoA-I clearance in the present study. Although it has not been investigated, atorvastatin-induced upregulation of candidate HDL receptors involved in holoparticle HDL uptake by tissues such as liver and kidney remains a theoretical possibility.…”
Section: Discussionmentioning
confidence: 56%
“…Atorvastatin appears to inhibit CETP activity in humans, which should decrease HDL triglycerides, 31 and fails to alter hepatic and lipoprotein lipase levels in the rabbit model, 22 which should leave the HDL triglyceride content unchanged. Nonetheless, triglyceride enrichment of HDL has previously been shown to enhance HDL apoA-I catabolism in vivo, 32 and combined with other drug-induced effects, could have contributed to the enhanced HDL apoA-I clearance in the present study. Although it has not been investigated, atorvastatin-induced upregulation of candidate HDL receptors involved in holoparticle HDL uptake by tissues such as liver and kidney remains a theoretical possibility.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, variations in LTIP activity sustain the rate of HDL 2 remodeling regardless of TG status. By retarding the enrichment of HDL 2 with TG, LTIP would stabilize these particles and prevent their premature clearance from plasma (60,61). Overall, our data show that LTIP regulates CETP-mediated remodeling of HDL in a subclass-specific manner.…”
Section: Ltip Binding To Ldl Hdlmentioning
confidence: 71%
“…Triglycerides in HDL, like in LDL, are a good substrate for hepatic lipase and the hydrolysis produces smaller particles and free apo A-I that is shed from the particle and cleared by the kidneys. Triglyceride enrichment of HDL has been ob- served to enhance in vivo clearance of HDL apo A-I in healthy men [145]. It has been shown that lipolysis of Tg enriched HDL particles by HL was required for the enhanced clearance rate of HDL [146].…”
Section: Mechanisms Behind Lowering Of Hdlmentioning
confidence: 99%